CIPP Evaluation Model of the P5-PPRA Program on Character Building - Himsyah, Unun Zumairoh Asr; Ariyanti, Novi (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2025)
The Projek Penguatan Profil Pelajar Pancasila dan Profil Pelajar Rahmatan lil ‘Alamin (P5-PPRA) program is an innovative learning method in the Merdeka Curriculum designed to shape students’ holistic character through project-based learning. Although this program has great potential in internalizing the noble values of Pancasila and religious moderation, its implementation and effectiveness in Islamic educational institutions, especially madrasah, have not been comprehensively evaluated. This study aims to evaluate the implementation of P5-PPRA at Madrasah Aliyah Al Ma’arif Singosari, Malang Regency, with a focus on the integration of Pancasila and Rahmatan lil ‘Alamin values and their impact on student character building. Using a qualitative approach with the CIPP (Context, Input, Process, Product) evaluation model, data were collected through interviews, observation, and documentation. The results showed that MA Al Ma’arif Singosari has successfully implemented P5-PPRA effectively, as seen from the mature needs analysis, resource readiness, structured implementation process, and product achievements in the formation of student character in line with Ahlussunnah Wal Jamaah values (Tawazun, Tawassuth, Tasammuh, I’tidal, Ta’addud, and Ta’awwun). This research contributes theoretically to the development of educational evaluation science, especially the application of the CIPP model in the context of Islamic education, and provides practical references for policy makers in designing relevant and sustainable character education programs.